The mom & pop store how the unsung heroes of the American economy are surviving and thriving - Spector, Robert 1947- (New York Walker & Company, 2009)
Business journalist Spector celebrates the history of small, independent retail stores and how mom and pop businesses across the country still thrive on attentive customer service and community support.
Working-class hero -- Perth Amboy -- Zeyde (grandfather) : founder of our family business -- The rise of the merchant -- Working alongside mom & pop -- Independence -- Passion and persistence -- Reinvention -- There goes the neighborhood -- Connection -- Hard times -- If your neighbor has it to sell.
CSSP-6510 donated by The Rotary Club, Beaverton, Oregon, United States of America.
Keywords: Couple-owned business enterprises -- United States -- History; Small business -- Social aspects -- United States -- History